Reproductive and Sexual Health Problems and Its Coping Mechanism among Adolescents and Youth with Disability of Bardia - Rana, R; Adhikari, S; Poudel, BP (2016)
Background: Adolescents and Youths with disabilities (AYDs) is one of important and the minority segment of Nepalese society and population. It is also marginalized from main stream of our society. On other hand, sexuality is still one of the taboos in our society. In this situation, AYDs may not bring out their sexual problems and talk with other people so that it can be prevented or minimize these problems in time. This study thus aims to identify the reproductive and sexual health problems among adolescents and youth with disabilities and find out coping mechanisms against these problems Methods: It was a descriptive and cross-sectional study. The study was undertaken in Bardia district of Nepal. A total of 6327 (projected population) was the population of people with disability. A sum of 350 AYDs was sampled by using purposive sampling method. It was a total of 10 AYDs from each VDC and 40 from one municipality. The data collection tool was Interview schedule. The data was collected in the month of May 2008 by trained and experienced enumerators. The collected data was analyzed by the help of SPSS. Simple statistical calculation i.e. frequency, percent, mean, median, standard deviation etc have been done for discussion of the data. Results: A total of 3 percent male and 19.3 percent female faced pressure for sexual contact. The coping mechanism against pressure were shouting/crying (60 percent and 31.4 percent respectively) complaining to family (25.7 percent female) becoming angry or showing angry face (14.3 percent female), request not to do so (40 percent male and 20 percent female) and complaining police (8.6 percent female). Only 3 percent male and 20.4 percent female were found sexually exploited. Various coping mechanism among AYDs were observed against sexual exploitation 40 percent male and 24.3 percent female used to ask help from other while, 40.5 percent and 8.1 percent females respectively used to run away and fighting. Similarly 40 percent male and 13.5 percent female used to request not to do so and finally 60 percent male and 37.8 percent female used to complaining to their friends. A total of 10.8 percent and 11.6 percent were perceived that they were infected by STDs. The sources of knowledge related to SRH were friends/peers (59.5 percent male and 46.4 percent female), family (15.4 percent male and 40.3 percent female), school/teachers (29 percent male and 17.7 percent female), neighbors/relatives (3.6 percent male and 6.6 percent female) and other like media, newspaper, book, advertisement (11.2 percent male and 4.4 percent female). Conclusions: The majorities of AYDs used to share their reproductive and sexual health problem with their friends, relatives and family members so the special and effective programs targeting to the AYDs should be carried out through peer approach as well as other collective or holistic method in various related issues i.e. sexual desire, exploitation, sexual dysfunction, STIs etc. AYDs were found doing nothing against some kind of problems which is not good because it can bring any big problem in the future so that they should be encouraged and made aware about health seeking behavior in time and they should be given enough information about the places where they get services about SRH. Keywords: adolescent and youth with disabilities; coping mechanisms; reproductive and sexual health problems.